A worker on the transcontinental railroad - Barter, James, 1946- (The working life series, 2003)
Describes the difficult lives of Transcontinental Railroad laborers, discussing camp life on both the Union and Central Pacific, specialty crews and special dangers, line crews, and camp dissatisfaction and unrest.